Kinetics of the thapsigargin-induced Ca2+ mobilisation: A quantitative analysis in the HEK-293 cell line - Pick, Tillman; Gamayun, Igor; Tinschert, René; Cavalié, Adolfo (Frontiers in Physiology, 2023)
Thapsigargin (TG) inhibits the sarco/endoplasmic reticulum Ca2+ ATPase (SERCA) pump and, when applied acutely, it initiates a Ca2+ mobilisation that begins with the loss of Ca2+ from the endoplasmic reticulum (ER) and culminates with store-operated Ca2+ entry (SOCE) from the extracellular space. Using the popular model cell line HEK-293, we quantified TG-induced changes in cytosolic and ER Ca2+ levels using FURA-2 and the FRET-based ER Ca2+ sensor D1ER, respectively. Our analysis predicts an ER Ca2+ leak of 5-6 µMs-1 for the typical basal ER Ca2+ level of 335-407 µM in HEK-293 cells. The resulting cytosolic Ca2+ transients reached peak amplitudes of 0.6-1.0 µM in the absence of external Ca2+ and were amplified by SOCE that amounted to 28-30 nMs-1 in 1 mM external Ca2+. Additionally, cytosolic Ca2+ transients were shaped by a Ca2+clearance of 10-13 nMs-1. Using puromycin (PURO), which enhances the ER Ca2+ leak, we show that TG-induced cytosolic Ca2+ transients are directly related to the ER Ca2+ levels and to the ER Ca2+ leak. A one-compartment model incorporating ER Ca2+ leak and cytosolic Ca2+ clearance accounted satisfactorily for the basic features of TG-induced Ca2+ transients and underpinned the rule that an increase in amplitude associated with shortening of TG-induced cytosolic Ca2+ transients most likely reflects an increase in ER Ca2+ leak.